2023
DOI: 10.1002/cbic.202300222
|View full text |Cite
|
Sign up to set email alerts
|

The [4Fe‐4S]‐Cluster of HydF is not Required for the Binding and Transfer of the Diiron Site of [FeFe]‐Hydrogenases

Abstract: The active site of [FeFe]‐hydrogenases contains a cubane [4Fe‐4S]‐cluster and a unique diiron cluster with biologically unusual CO and CN− ligands. The biogenesis of this diiron site, termed [2FeH], requires the maturation proteins HydE, HydF and HydG. During the maturation process HydF serves as a scaffold protein for the final assembly steps and the subsequent transfer of the [2FeH] precursor, termed [2FeP], to the [FeFe]‐hydrogenase. The binding site of [2FeP] in HydF has not been elucidated, however, the [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…However, a recent report showed that synthetic [2Fe] F can bind to HydF and activate HydA even in the absence of the [4Fe–4S] cluster. 39 Further studies are needed to determine the details of how [2Fe] E binds to HydF, and specifically whether [2Fe] E binds directly to the [4Fe–4S] cluster of HydF.…”
mentioning
confidence: 99%
“…However, a recent report showed that synthetic [2Fe] F can bind to HydF and activate HydA even in the absence of the [4Fe–4S] cluster. 39 Further studies are needed to determine the details of how [2Fe] E binds to HydF, and specifically whether [2Fe] E binds directly to the [4Fe–4S] cluster of HydF.…”
mentioning
confidence: 99%
“…Although this exchange did not result in significant changes in the FTIR-spectrum, the overall cluster occupancy was moderately reduced to 64%. In addition, the second CN – -ligand is in close distance to the [4Fe-4S]-cluster in our model, which is in agreement with recently published results that suggested a close proximity of one CN – -ligand to the [4Fe-4S]-cluster …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the second CN − -ligand is in close distance to the [4Fe-4S]-cluster in our model, which is in agreement with recently published results that suggested a close proximity of one CN − -ligand to the [4Fe-4S]-cluster. 33 Located on the other site of the cavity and positioned toward the adt-bridge of [2Fe] F , there is a highly conserved DIG-motif (conservation degree: D: 100%, I: 100% and G: 93). The high conservation degree and the surface exposed location of these residues suit a possible role during adt synthesis or its coordination.…”
Section: Suggesting a New Binding Model Of [2fe] F In Hydfmentioning
confidence: 99%
See 2 more Smart Citations